Frequency of oral Lichen Planus among hypothyroid patients - Baharvand, Maryam; Hamrahi , Farzaneh; Gholami, Shahzad; Hajighasem, Parisa (Brazilian Dental Science, 2022)
Objective: Recent investigations have suggested a correlation between thyroid diseases, particularly hypothyroidism (HT), and oral lichen planus (OLP). Objective: This study aimed to assess the frequency of OLP in HT patients. Material and Methods: This analytical descriptive study evaluated 100 HT patients including 94 females and 6 males, who were selected by convenience sampling. The subjects were clinically examined for OLP. The mean age of patients was 42.49±1.29 years. Also, 100 age- and sex-matched healthy controls were examined. The data were analyzed using chi-square test and Fisher’s exact test via SPSS. Results: Of all, 14 (14%) HT patients (12 females and 2 males) had OLP while only one case of OLP was found in the control group. The difference between the two groups in the frequency of OLP was significant (P=0.001). The odds ratio (OR) of developing OLP was calculated to be 16.11 in HT patients. Reticular form was the most common type of OLP in patients (50%). The buccal mucosa was the most common site of involvement (92.85%). The mean age of patients with OLP was 42.93±1.29 years with a median of 46±1.29 years in HT group. Conclusion: The frequency of OLP was significantly higher in HT patients such that HT patients had higher odds of developing OLP by 16 folds. KEYWORDS Hypothyroidism; Oral lichen planus; Frequency; Comparison.